Pendampingan Teknis Cara Pemasangan Bronjong di Dusun Sukuh Kabupaten Karanganyar - Cahyono, Dhamang Budi; Widiatmoko, Kukuh Wisnuaji; Mahmud, Faizal; Crista, Ngudi Hari (Jurnal Pengabdian KOLABORATIF, 2025)
Landslides are a frequent natural disaster in the Karanganyar area, especially in hilly areas with high rainfall and fragile geological conditions. This community service activity aims to provide technical assistance on gabion installation as a landslide mitigation effort in Dusun Sukuh, Ngargoyoso District, Karanganyar Regency. The method includes lectures, demonstrations, and direct practice, covering preparation stages, material selection, and correct installation techniques. The results showed a significant increase in participants' understanding, from an average pre-test score of 32% to 70% in the post-test. This indicates that the program effectively improved the knowledge and skills of the community regarding gabion installation techniques. The community showed active participation and high enthusiasm, reflecting their awareness of the importance of disaster mitigation efforts. This activity is expected to support the sustainability of community-based disaster risk reduction efforts in the region.
Keywords: community empowerment; gabion installation; landslide mitigation; technical assistance